2017
DOI: 10.6065/apem.2017.22.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of gonadotropin-releasing hormone agonist in obese girls with central precocious puberty

Abstract: Purpose This study investigated the influence of obesity on the clinical course and effect of gonadotropin-releasing hormone analog (GnRHa) treatment in girls with central precocious puberty (CPP).Methods Medical records of 182 girls with CPP treated with GnRHa were reviewed. They were divided into 2 groups: normal weight (n=108) and overweight/obesity (n=74). Chronological age (CA), bone age (BA), difference between BA and CA (BA–CA), standard deviation score (SDS) of height, body mass index (BMI), predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Thus, even if GnRHa use is not associated with increases in BMI SDS, there is a need for counseling and intervention regarding healthy diet and lifestyle for many children with CPP and their families. Given data indicating that some nonobese girls may also experience a transient increase in BMI SDS with initiation of GnRHa therapy, the need for lifestyle counseling may also be relevant to nonobese children with CPP to help ensure any increases do not persist posttreatment [ 81 , 84 , 89 , 95 , 101-104 ]. Long-term studies of treated girls with CPP provide reassurance that treatment is not associated with increased risk of obesity or poor metabolic outcomes [ 95 , 104 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…Thus, even if GnRHa use is not associated with increases in BMI SDS, there is a need for counseling and intervention regarding healthy diet and lifestyle for many children with CPP and their families. Given data indicating that some nonobese girls may also experience a transient increase in BMI SDS with initiation of GnRHa therapy, the need for lifestyle counseling may also be relevant to nonobese children with CPP to help ensure any increases do not persist posttreatment [ 81 , 84 , 89 , 95 , 101-104 ]. Long-term studies of treated girls with CPP provide reassurance that treatment is not associated with increased risk of obesity or poor metabolic outcomes [ 95 , 104 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…Some studies have reported an association between GnRHa treatment and body mass index (BMI) increase (9,(11)(12)(13), in previously normal-weight girls (14,15) as well as in those with obesity (16). Other studies have found no influence of GnRHa treatment on weight status (8,17,18), and recently, it has been proposed that the increase of BMI occurs during treatment but reverts to baseline after GnRHa is discontinued (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Về hiệu quả của GnRH trên chiều cao, hầu hết các nghiên cứu đều kết luận rằng mặc dù nhóm trẻ béo phì có tuổi xương tiến triển hơn nhưng việc sử dụng GnRHa vẫn giúp làm chậm tiến triển tuổi xương, cho phép đạt được chiều cao cuối cùng phù hợp với chiều cao trung bình theo bố mẹ (MPH) [25][26][27][28][29].…”
Section: Hiệu Quả Của đồNg Vận Gnrh Trong đIều Trị Dtstu Cho Trẻ Thừa...unclassified